Gender differences in skilled performance under failure competitive environments: evidence from elite archers - Li, C.; Zhao, Y. (Frontiers in Psychology, 2024)
Introduction: Psychologists are particularly interested in how people operate in stressful settings. The sporting arena is a "natural laboratory" for studying how people behave and perform in high-pressure situations. This study explores the gender differences in archers` ability to cope with adversity, highlighting the significant cold-hand effect observed in both male and female archers, with notable differences in the last arrow performance under pressure.